Epistemicide: the Roman Case - Peralta, Dan-el Padilla (Classica - Revista Brasileira de Estudos Clássicos, 2020)
The desire to recover and preserve the antiquity that in some circles is designated as “classical” is rooted in the conviction that knowledge of that antiquity is a good. But does (or should) awareness of the epistemicides that define Greco-Roman antiquity modify the texture of that desire? Relying on the definition of epistemicide proposed by the postcolonial theorist Boaventura de Sousa Santos, this article argues that the Roman Republic and Empire engineered a staggering loss of epistemic diversity throughout the ancient Mediterranean, traceable along multiple vectors — from mass enslavement to ecological upheaval. It concludes with a summons to come to terms with the scope of ancient Rome’s epistemicide, and to embrace the epistemological and ethical recalibration needed to write its history.